Stand Height/Site Index Equations for Jack Pine and Black Spruce Trees Grown in Natural Stands. Issue 1 (27th April 2017) - Sharma, Mahadev; Reid, Douglas E B
Abstract: Stand/top height equations were developed for jack pine ( Pinus banksiana Lamb.) and black spruce ( Picea mariana Mill. B.S.P.) trees grown in natural stands in the boreal forest region of northwestern Ontario, Canada. Data used in this study came from stem analysis on three to five dominant or codominant trees sampled from 383 plots for jack pine and 211 plots for black spruce. Equations were fitted using a nonlinear mixed-effects approach. For both species, adding random effects to the parameters in the height growth model significantly improved fit statistics. The autocorrelation problem in the data sets was addressed using first-order autoregressive structure. An independent data set from across the boreal regions of northern Ontario was used to evaluate the predictive accuracy of the height growth models. The model with random effects that account for autocorrelation had slightly better predictive accuracy than the one without specifying random effects and autocorrelation. The models developed here can be used to make informed forest management decisions by estimating stand height at any age, given height at a point in time. Site index of a plot/stand can be estimated using the same model by calculating height at a given base (index) age. We suggest using breast-height age 50 years as the base age for determining site index for both species in Ontario because this is near midrotation for most managed stands that are not density regulated. The height growth models developed for natural stands were compared with recently published models for (density-regulated) plantations of the same two species. The models for natural stands were not similar to the ones for plantations.